Psychological status and quality of life in patients with sick sinus syndrome and ischemic chronic heart failure - A. E. Кutuzova; N. N. Burova; N. P. Alexeeva; N. N. Petrova (Российский кардиологический журнал, 2005)
Sick sinus syndrome (SSS) and chronic heart failure (CHF) are combined quite often, that explains the need for complex study of their effects on adaptation status in such patients. To assess quality of life (QoL) and psychological status inpatients with SSS and ischemic CHF. Six-minute walking test was performed; depression, anxiety, alexithymia levels, QoL, coping mechanisms and lifestyle index were assessed in 75patients with coronary heart disease (CHD), associated with NYHA class I-II CHF, with or without SSS. Ln CHF patients, no additional adverse effects of SSS on somatic, psychological status and QoL were observed.